Implementation of Pancasila Values in School Culture in the Era of Globalization - Indah Sari; Nova Siswanti Adtya; Pinasti Haningtyas; Syifa Rahmatillah; Ruth Manalu; Afandi Afandi (IJRAEL: International Journal of Religion Education and Law, 2023)
As the ideology of the nation and state, Pancasila reflects the customary, cultural and religious values embodied in the life of the Indonesian people. In addition, Pancasila is also used as a basis for building the Unitary State of the Republic of Indonesia. The values in Pancasila include divinity, humanity, unity, democracy and justice. The current condition of Indonesian education can be seen from the behavior and character of students and educators inside and outside the educational environment. As a state ideology, Pancasila faces various challenges from time to time. To maintain the existence of Pancasila as the state ideology, especially in the era of the industrial revolution 4.0, the implementation of Pancasila values in everyday life, especially in education, is necessary. This study used a descriptive qualitative approach with data collection techniques in the form of literature study and inductive data analysis. The data source consists of the results of previous research, but reviewed again in this journal. Globalization cannot be avoided, so Pancasila is needed as a filter to deal with it. Cultivating Pancasila values must not only be understood, but also internalized and realized in the experiences of every individual and the whole society, especially students, most of whom currently hold the key to the successful implementation of the five precepts of Pancasila so that a person who grows with awareness and encourages the implementation of life can be formed. social, just, and state based on Pancasila.